Research on Tobacco in India (including the Betel Quid and Areca Nut) : An Annotated Bibliography of Research on Use, Health Effects, Economics, and Control Efforts - Stewart Ray, Cecily; Gupta, Prakash; de Beyer, Joy (World Bank, Washington, DC, 2013)
This report is a compilation of references and abstracts of all research on tobacco in India from 1985 to 2003. Studies are organized by subject matter, and within each sub-topic, are arranged by year of publication with most recent studies listed first, and for studies published in the same year, alphabetically by author's last name. The studies include tobacco use surveys, studies on tobacco-related mortality, tobacco-related diseases both cancerous and non-cancerous, according to body system and site, and other health problems associated with tobacco use and environmental tobacco smoke. Other topics include the toxicity of tobacco products, educational interventions and the psychology of tobacco use, tobacco control measures and policies, reports on tobacco advertising and sponsorship and research into the tobacco health hazards faced by tobacco workers. It also includes studies on tobacco employment, tobacco growing and technology, and the economics of tobacco. The following databases were searched: Pub Med, Medline, and J-Gate (a new Indian database). The keywords used for the searches were '(Tobacco OR smoking) AND India', as well as names of diseases known from international research findings to be associated with tobacco, 'AND India'. In some cases, reports were excluded if they were duplicative, or the methodology or findings were unclear.